KONSEP STRES AKADEMIK DAN IMPLIKASINYA TERHADAP PERILAKU BELAJAR SISWA - Windy Ana Fitriyanti (Al-Kindi, 2025)
Academic stress is a psychological condition experienced by students in response to pressures within the learning environment, such as assignments, exams, academic competition, and expectations from parents and teachers. The concept of academic stress encompasses various aspects, including emotional pressure, cognitive load, and physical tension, all of which can affect students' mental health and learning behavior. This study aims to examine the concept of academic stress and its implications for students’ learning behavior in school settings. Using a qualitative literature study approach, this research reviews educational psychology theories and relevant research findings. The results indicate that academic stress negatively impacts students’ concentration, learning motivation, and productivity. In the long term, unmanaged stress may lead to avoidance behavior, anxiety, and even academic burnout. Therefore, it is essential for educators and parents to understand the sources of academic stress and develop learning strategies that support students’ mental well-being, in order to foster positive and sustainable learning behavior.